The prevalence of dyslipidemia and its correlation with anti-retroviral therapy among people living with HIV in China: a systematic review and meta-analysis - Wenjing, Zhai; Fei, Ouyang; Shenao, Zhan; Yu, Huang; Gengfeng, Fu; Haitao, Yang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDyslipidemia, a risk factor of cardiovascular diseases, was a long-term adverse event of anti-retroviral drugs. Efavirenz (EFV) and lopinavir/ritonavir (LPV/r) were recommended and the widely used antiretroviral drugs while the proportion of taking integrase strand transfer inhibitors (INSTI)-based regimens are increasing recently in China. Regarding to the large population of people living with HIV (PLWH) in China and the regional fluctuations in prevalence of dyslipidemia, this meta-analysis aims to evaluate the prevalence of dyslipidemia and its correlation with anti-retroviral therapy (ART) among PLWH in China, especially the impact of LPV/r, EFV and INSTI-based regimens.MethodsWe searched English and Chinese databases using MeSH terms to identify all relevant articles. The study participants were divided into ART-naïve and ART-experienced PLWH. The prevalence of dyslipidemia and mean difference of serum lipids were estimated using random-effects models. Subgroup analysis and univariate meta-regression were conducted to evaluate factors associated with prevalence of dyslipidemia among ART-experienced PLWH.ResultsIn this meta-analysis, we found dyslipidemia prevalence of 49.8% and 55.1% among ART-naïve and experienced PLWH in China. Elevated triglycerides(TG) and reduced high-density lipoprotein cholesterol (HDL-C) were the most prevalent dyslipidemia, irrespective of ART experience. Dyslipidemia was more common in PLWH residing in South China, with baseline CD4 cell count over 500 cells/μl or with a BMI ≥ 24 kg/m2. Notably, Traditional Chinese medicine adjuvant therapy was associated with higher prevalence of dyslipidemia. Moreover, INSTI-based regimens were significantly linked to higher prevalence of low HDL-C compared to other regimens.ConclusionsThe routine assessment of lipid profiles should be advised among PLWH before and after the initiation of ART in China, especially in patients on INSTI-based regiments. Moreover, early interventions, including physical activity, dietary adjustments, and optimization of ART regimens, should be considered when the dyslipidemia is diagnosed in PLWH.